2012
DOI: 10.1016/j.molcel.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

IKKα Activation of NOTCH Links Tumorigenesis via FOXA2 Suppression

Abstract: SUMMARY Pro-inflammatory cytokine TNFα plays critical roles in promoting malignant cell proliferation, angiogenesis, and tumor metastasis in many cancers. However, the mechanism of TNFα-mediated tumor development remains unclear. Here, we show that IKKα, an important downstream kinase of TNFα, interacts with and phosphorylates FOXA2 at S107/ S111, thereby suppressing FOXA2 transactivation activity, leading to decreased NUMB expression and further activates the downstream NOTCH pathway and promotes cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 41 publications
4
74
0
Order By: Relevance
“…Of every cell type, 10 7 cells of extracted nuclear proteins from each condition were denatured by boiling at 95°C for 10 min. 1D gel electrophoresis was as de scribed previously (Liu et al, 2012) and performed with 10% SDS PAGE. After the gel was stained using VisPRO 5 min protein stain kit (VP01 500; Visual Protein), every lane was cut off into 10 equal sections, followed by re duction with  mercaptoethanol (1% vol/vol) in 25 mM ammonium bicar bonate at room temperature in the dark for 20 min, and alkylation with 5% vol/vol 4 vinylpyridine in 25 mM ammonium bicarbonate for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Of every cell type, 10 7 cells of extracted nuclear proteins from each condition were denatured by boiling at 95°C for 10 min. 1D gel electrophoresis was as de scribed previously (Liu et al, 2012) and performed with 10% SDS PAGE. After the gel was stained using VisPRO 5 min protein stain kit (VP01 500; Visual Protein), every lane was cut off into 10 equal sections, followed by re duction with  mercaptoethanol (1% vol/vol) in 25 mM ammonium bicar bonate at room temperature in the dark for 20 min, and alkylation with 5% vol/vol 4 vinylpyridine in 25 mM ammonium bicarbonate for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Notch signaling pathway is known to promote various types of human tumors, such as hepatocellular carcinoma (HCC) and breast cancer [4][5][6]. The Notch pathway comprises a family of transmembrane receptors and ligands, modifiers and transcription factors [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Notch pathway comprises a family of transmembrane receptors and ligands, modifiers and transcription factors [7]. Following activation of the Notch pathway, the Notch intracellular domain (NIC) translocates to the nucleus to activate transcription of target genes [4]. Aberrant activation of the Notch pathway leads to various diseases including cancer [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Conserved helix-loop-helix ubiquitous kinase (IKKa) is a direct target of miR-148a, which binds to the 3'UTR site of IKKa mRNA. It has been reported that IKKα may mediate Notch signaling activation through regulation of NUMB, Endocytic Adaptor Protein (NUMB), as NUMB may inhibit Notch signaling in HCC (59)(60)(61). The silencing of IKKa may induce hepatocytic differentiation, a similar effect to the upregulation of miR-148, whilst the overexpression of Notch2 may reverse this phenomenon (58).…”
Section: Gastric Cancermentioning
confidence: 99%